2010
DOI: 10.1037/a0018680
|View full text |Cite
|
Sign up to set email alerts
|

Age effect on components of episodic memory and feature binding: A virtual reality study.

Abstract: We view these results as an indication that virtual environments could provide helpful standard tools for assessing age effects on the main aspects of episodic memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
111
2
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(127 citation statements)
references
References 76 publications
9
111
2
5
Order By: Relevance
“…The WWW test explicitly requires the ability to bind spatiotemporal features. This binding process has been shown to be specifically affected by the aging process and is predictive of selfreported everyday memory impairment in a way that individual what, where, and when elements, as well as word-list FR, are not (Plancher et al 2010). By contrast, the UQ/SM task explicitly requires the ability to reanalyze previous experiences for new information, something not required by the other tasks.…”
Section: Discussionmentioning
confidence: 99%
“…The WWW test explicitly requires the ability to bind spatiotemporal features. This binding process has been shown to be specifically affected by the aging process and is predictive of selfreported everyday memory impairment in a way that individual what, where, and when elements, as well as word-list FR, are not (Plancher et al 2010). By contrast, the UQ/SM task explicitly requires the ability to reanalyze previous experiences for new information, something not required by the other tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in humans have shown that WWW memories are reliably reported as "remembered" rather than "known" (Holland and Smulders 2011;Easton et al 2012;Cheke and Clayton 2013) and are correlated with, but distinct from, free recall performance Clayton 2013, 2015;Mazurek et al 2015). However, evidence for aging effects using WWW is mixed (Plancher et al 2010(Plancher et al , 2012Mazurek et al 2015).The treasure-hunt task further differs from other episodic memory tests because the encoding period allows individuals to "hide" items themselves . This is significant because agentic involvement in the encoding of items aids recollection (Plancher et al 2012) and gets closer to memory encoding in everyday life (one does not passively observe the location of one's keys, but actively places them).…”
mentioning
confidence: 93%
“…Recent studies in humans have shown that WWW memories are reliably reported as "remembered" rather than "known" (Holland and Smulders 2011;Easton et al 2012;Cheke and Clayton 2013) and are correlated with, but distinct from, free recall performance Clayton 2013, 2015;Mazurek et al 2015). However, evidence for aging effects using WWW is mixed (Plancher et al 2010(Plancher et al , 2012Mazurek et al 2015).…”
mentioning
confidence: 97%
“…Recent advances have made it possible to overcome the limitations of standard laboratory tasks by implementing M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 4 virtual reality (VR), where the subject is immersed in a virtual environment and interacts with it by acting on its components. Specifically, VR enables laboratory situations close to daily life yet allowing experimental control, and has already been successfully used to address issues regarding for instance spatial navigation (Doeller, et al, 2012, Grasso, et al, 2000 and episodic memory (Matheis, et al, 2007, Plancher, et al, 2013, in healthy or diseased aged subjects (Plancher, et al, 2010, Plancher, et al, 2012. To this day, the few behavioral studies that have used VR to examine PM (Canty, et al, 2014, Kalpouzos, et al, 2010, Sweeney, et al, 2010 concur that by providing an analogue of controlled everyday situations, VR may offer better insights into PM either in normal or brain-damaged subjects.…”
Section: Introductionmentioning
confidence: 99%